2010
DOI: 10.1586/ern.09.148
|View full text |Cite
|
Sign up to set email alerts
|

Role of dopamine in the pathophysiology and treatment of obsessive–compulsive disorder

Abstract: The differential effects of serotonin-reuptake inhibitors on obsessive-compulsive disorder (OCD) were sufficient to presume that a serotonin regulatory disorder is the most essential part of the pathophysiology of OCD. In patients with OCD, however, a high-dose of serotonin-reuptake inhibitor monotherapy may not be sufficient, and approximately half of patients were noted to be treatment-resistant. As results from previous studies have shown, there have been positive treatment responses to the dopaminergic ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 126 publications
0
71
0
3
Order By: Relevance
“…12 This is consistent with a range of data pointing to an important role for the dopamine system in OCD. 13 Alterations in the dopaminergic system may reflect the influence of particular environmental factors (e.g., exposure to stress or adversity) 14 or particular genetic factors (e.g., functional variants in the dopamine system). 15 However, although OCD is considered a polygenic disorder, 16 the particular association of symmetryrelated symptomatology, early adversity, and selected polymorphisms in dopaminergic genes has, to our knowledge, not been investigated in this condition.…”
Section: Introductionmentioning
confidence: 99%
“…12 This is consistent with a range of data pointing to an important role for the dopamine system in OCD. 13 Alterations in the dopaminergic system may reflect the influence of particular environmental factors (e.g., exposure to stress or adversity) 14 or particular genetic factors (e.g., functional variants in the dopamine system). 15 However, although OCD is considered a polygenic disorder, 16 the particular association of symmetryrelated symptomatology, early adversity, and selected polymorphisms in dopaminergic genes has, to our knowledge, not been investigated in this condition.…”
Section: Introductionmentioning
confidence: 99%
“…1 ) [71] . As previously discussed, since OCD patients are thought to have impaired serotonin signaling, it is possible that this deficiency is leading to dopaminergic hyperactivity, characteristic of OCD [65] .…”
Section: Dopamine In Ocdmentioning
confidence: 97%
“…Although numerous studies have demonstrated the effectiveness of SRIs as a primary treatment option for OCD, there appears to be a subset of OCD patients that are resistant to SRI treatment [65] . Furthermore, pharmacological challenge studies of the serotonin system, as well as studies measuring serotonin metabolite levels in the CSF have not always shown consistent results [66] .…”
Section: Estradiol and Serotoninmentioning
confidence: 99%
See 2 more Smart Citations